Iran, Iraq, and the Legacies of War: By Lawrence G. Potter and Gary G. Sick, eds. (New York: Palgrave Macmillan, 2004. 224 pages.) (American Journal of Islam and Society, 2006)
With the noble aims of conflict resolution and peace building, Lawrence G.Potter and Gary G. Sick have compiled an excellent collection of essays on“the war without winners” (p. 2). This remarkable publication, Iran, Iraq,and the Legacies of War, adds to Potter and Sick’s series of co-edited bookson Middle Eastern issues, namely, The Persian Gulf at the Millennium:Essays in Politics, Economy, Security, and Religion (Palgrave Macmillan:1997) and Security in the Persian Gulf: Origins, Obstacles, and the Searchfor Consensus (Palgrave Macmillan: 2002). Potter and Sick are two prominentscholars of international affairs at Columbia University. During theCarter presidency, Sick served as the principal White House aide for Iran onthe National Security Council. (Sick is well-known for his exposé All FallDown: America’s Tragic Encounter with Iran [Random House: 1985]).This 224-page book was written in the cautiously hopeful belief thatthe time has come for reconciliation to begin. It contains nine chapters plusPotter and Sick’s helpful introduction, which contextualizes the futile warthat shook the world. The Iran-Iraq war was one of the longest and costliestconventional wars of the twentieth century. Although the number ofcasualties is still in dispute, an estimated 400,000 were killed and perhaps700,000 were wounded on both sides (p. 2). The Economist commentedthat “this was a war that should never have been fought … neither sidegained a thing, except the saving of its own regime. And neither regime wasworth the sacrifice” (p. 2) ...